Pengaruh Gaya Kepemimpinan, Stres Kerja, Beban Kerja Terhadap Kepuasan Kerja Dalam Meningkatkan Kinerja Karyawan Pada Universitas Jember - Nining Ratno Himawati (RELASI : JURNAL EKONOMI, 2016)
The purpose of this study is to analyze and prove the influence of leadership style, job stress, workload on job satisfaction in improving the performance of employees at the University of Jember. Total population of 548 people is taken from employees Bureau I, II Bureau and Bureau III at the University of Jember. The total sample of 125 respondents drawn using proportional random sampling technique sampling, and data analysis techniques using Structural Equation Modeling (SEM) with the help of AMOS software. The results of the study explained that occurred a significant effect on the latent exogenous variables that influence leadership style, job stress, workload against intervening variable is satisfaction in improving the performance of (endogenous latent variables). This is demonstrated by the significant figures and valid in every model tested.